DAMPAK EKONOMI DESA MELALUI WISATA PANTAI WANE DALAM PERSPEKTIF EKONOMI ISLAM KEC. MONTA, KAB. BIMA - Nurwati (AL-MUJADDID - JURNAL EKONOMI DAN BISNIS ISLAM, 2025)
This study aims to determine the impact of the village economy through wane beach tourism in the perspective of Islamic economics in Monta District, Bima Regency. The study used a desk research method with online data and information search techniques, secondary sources, and scientific publication sources. While the analysis technique used is qualitative descriptive analysis techniques, analogies, comparisons of several research results and other scientific publications with the problem of the village economic dimension through tourist beaches. The results of the study showed that there are two aspects in the first village economy, namely the positive aspect for the village economy, increasing village economic income, making the village more exposed, asphalted transportation roads, increasing household economy, fishermen have the opportunity to sell fish. The Islamic economic view of the impact of tourist villages focuses on welfare, justice, and utilizing the environment without damaging the environment. While the negative aspects for the village economy are the lack of village security, the high crime rate among visitors so that it hinders local tourists from visiting and will reduce village income. In the Islamic economic view, it is very condemnatory of unjust acts and crime rates that cause harm to others.